2015
DOI: 10.1007/s00167-015-3557-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after high-flex versus conventional total knee arthroplasty

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Several large-scale RCTs have been performed recently evaluating outcome after primary TKA [2,[5][6][7]10]. Patient-reported outcome of these studies gives a postoperative OKS of 33-35, which is comparable to the outcome we have found in our patients after simultaneous TKA and osteotomy.…”
Section: Discussionsupporting
confidence: 81%
“…Several large-scale RCTs have been performed recently evaluating outcome after primary TKA [2,[5][6][7]10]. Patient-reported outcome of these studies gives a postoperative OKS of 33-35, which is comparable to the outcome we have found in our patients after simultaneous TKA and osteotomy.…”
Section: Discussionsupporting
confidence: 81%
“…Although navigation has enhanced the accuracy of the component position and overall leg alignment [13, 16], it did not improve patient satisfaction or ROM in most studies [12, 18]. Latest techniques including partially navigated modified gap‐balancing techniques [2], PCL preservation [25] and newer implants like custom fit [23] or high‐flex implants [1] could not achieve a significant improvement in PRO or ROM either.…”
Section: Discussionmentioning
confidence: 99%
“…Total hip and knee arthroplasty (THA and TKA) are well-proven solutions in case of end-stage osteoarthritis of hip and knee 1 - 5 . Although, presence of complications can be devastating for the patient, especially periprosthetic joint infection (PJI) 6 - 8 .…”
Section: Introductionmentioning
confidence: 99%